2017
DOI: 10.1108/jgr-02-2017-0007
|View full text |Cite
|
Sign up to set email alerts
|

The rationale for responsible supply chain management and stakeholder engagement

Abstract: PurposeFirms are increasingly resorting to responsible supply chain management as they align their economic success with socially-responsible initiatives in their value chain. This contribution suggests that there are opportunities for global corporations who are keen on integrating responsible practices into their business operations. It is in their interest to report about their responsible supply chain management, social performance and sustainable innovations to their stakeholders. Design/methodology/appro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
4

Relationship

3
5

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 111 publications
0
9
0
Order By: Relevance
“…This adds up to GBP 133 billion or USD 161 billion worth of food that ends in the land fill. The Association of Hotels, Restaurants, and Cafes in Europe (HOTREC) and the European Federation of Food Banks (FEBA) are continuously educating stakeholders on ways of how to reduce food loss and waste from the hospitality industry's supply chains [44]. HOTREC promotes responsible food production and consumption behaviors among its members, including small and medium sized enterprises (SMEs).…”
Section: Responsible Practices To Prevent Food Loss and Wastementioning
confidence: 99%
See 1 more Smart Citation
“…This adds up to GBP 133 billion or USD 161 billion worth of food that ends in the land fill. The Association of Hotels, Restaurants, and Cafes in Europe (HOTREC) and the European Federation of Food Banks (FEBA) are continuously educating stakeholders on ways of how to reduce food loss and waste from the hospitality industry's supply chains [44]. HOTREC promotes responsible food production and consumption behaviors among its members, including small and medium sized enterprises (SMEs).…”
Section: Responsible Practices To Prevent Food Loss and Wastementioning
confidence: 99%
“…Hence, food and beverage preparers have to use them before their decay. Therefore, hospitality businesses ought to establish flexible arrangements with local suppliers and distributors to adjust their ordered quantities according to their expected number of customers (if possible) [44]. In 2019, Hilton reported that some of its properties reduced food waste by purchasing locally sourced, seasonal products, by working closely with "imperfect" suppliers, and by using the whole product wherever possible.…”
Section: Local Procurement Of Productsmentioning
confidence: 99%
“…Busse et al (2017) highlight the need to review stakeholder relationships to understand the supply chain risk. Previous reviews also focused on individual roles such as network exchange brokers (Saunders et al, 2017), while Camilleri (2017b) specifically points to future research regarding the collaboration with governments and regulatory authorities and impacts on consumers.…”
Section: Management Of Conflict Mineralsmentioning
confidence: 99%
“…. (2016),Fritz et al (2016),Gonzalez-Padron (2016),Gualandris et al (2015),Hawkins et al (2011), Hofmann et al (2015,Osuji (2015),Rotter et al (2014),Sutherland (2016),Fritz et al (2017),Akisik and Gal (2017),Camilleri (2017b),Busse et al (2017),Gold and Schleper (2017),Murray (2017),Saunders et al (2017), Timmer and Kaufmann (2017) Institutional theory 13 Carrigan et al (2017), Haan and Geenen (2016), Gold et al (2015), Hilson et al (2016), Hofmann et al (2015), Hyatt and Johnson (2016), McQuilken (2016), Osuji (2015), Rotter et al (2014), Schrempf-Stirling (2016), Zulu and Wilson (2012), Ansari and Kant (2017b), Sauer and Seuring (2017), Camilleri (2017a) Supply chain theory 11 Carter et al (2015), Fritz et al (2016), Gualandris et al (2015), Hawkins et al (2011), Hyatt and Johnson (2016), Timmer and Kaufmann (2017), Ansari and Kant (2017a), Sauer and Seuring (2017), Busse et al (2017), Gold and Schleper (2017), Ansari and Kant (2017b) Resource-based view 8 DeKoninck (2015), Bleischwitz et al (2012), Gold et al (2015), Gonzalez-Padron (2016), Hofmann et al (2015), Sarkis (2012), Timmer and Kaufmann (2017), Akhavan and Beckmann (. (2016), Young (2015), Dubey et al (2017) Contingency theory 2 Gold et al (2015), Hawkins et al (2011) (Corporate) governance theory 2 Paterno (2016), Schrempf-Stirling (2016) Social network theory 2 Hyatt and Johnson (2016), Saunders et al (2017) Economic theory 2 Moore (2017), Drielsma et al (2016) Agency theory 2 Moore (2017), Akemu et al (2016)…”
mentioning
confidence: 99%
“…SMEs do not engage in CSR activities if they receive less appreciation for their CSR deeds due to their trivial existence (Lee, Herold and Yu, 2016). Additionally, the absence or lax enforcement of regulations in developing and under-developed countries can influence SMEs to avoid adopting sustainable practices to gain monetary gains (Camilleri, 2017; Shi, Peng, Liu and Zhong, 2008).…”
Section: Literature Review: Barriers To Socially Responsible Supply Chains In Small- and Medium-sized Enterprisesmentioning
confidence: 99%